Design of a Web-Based Ordering Information System for the Legendary Ketan Restaurant in Tegal City - Maulana, Ikbal; Mutiara Handayani Ujianti (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The owner of Ketan Legendaris Restaurant in Tegal City also operates two other businesses, Mie Ayam Jhaya Baroe and Cafe Kopi PDKT, all of which are located within the same area. This setup often leads to challenges during peak times, such as unorganized order queues, accumulated orders, and delayed deliveries. Additionally, the restaurant's ordering system remains manual, relying on conventional record-keeping methods, which results in inefficient service and prolonged waiting times for customers. This research aims to design a web-based ordering information system to enhance the efficiency and effectiveness of the ordering process at Ketan Legendaris Restaurant. Data collection methods include direct observation, interviews, and library research. The analysis phase is conducted through several stages: surveying the existing system, analyzing survey findings, identifying information needs, and determining system requirements. The system design adopts the Waterfall model, utilizing UML diagrams as a tool for system modeling. MySQL is employed as the database, while the CodeIgniter framework is used to develop the web-based system using PHP. The research outputs a prototype of a web-based ordering information system designed to address the existing issues and improve the restaurant's operational performance. This system is expected to streamline the ordering process, making it faster, more organized, and accurate, thereby enhancing customer satisfaction and supporting the overall efficiency of the restaurant operations.